Correlation between Hashimoto’s thyroiditis and polycystic ovary syndrome: A systematic review and meta-analysis - Hu, Xiaojie; Chen, Yuquan; Shen, Yiting; Zhou, Siyuan; Fei, Wenting; Yang, Yuxin; Que, Huafa (Frontiers in Endocrinology, 2022)
Objective: A growing body of research suggests that patients with polycystic ovary syndrome (PCOS) may be at increased risk of developing Hashimoto's thyroiditis (HT), and having both conditions can make the condition worse. However, current research views are not uniform. Therefore, to explore the link between PCOS and HT, we conducted this study. Methods: We searched the Pubmed and Embase databases from the start of the search until August 2022. After rigorous screening by two authors, we finally identified 20 studies and independently extracted the data information required for this study. Results: A total of 92 articles were retrieved, duplicates and non-compliant articles were removed, and a total of 20 articles were finally included in the study. The results of the study showed that the proportion of PCOS patients with HT was higher than that of non-PCOS patients, and the proportion of HT patients with PCOS was higher than that of non-HT patients. Conclusions: This meta-analysis suggests that patients with PCOS are at increased risk of developing HT, and patients with HT are also at increased risk of developing PCOS